La soldadura de arco eléctrico como técnica escultórica - Parrales Almeida, Oscar Ramón (Machala : Universidad Técnica De Machala, 2021)
The present project is directed to the realization of a work with investigative character, with the purpose of leaving a guide for the people who are interested in the metal sculpture with the technique of the electric arc welding; starting with the summary of the writing it was realized in four chapters; in each one we detail the investigative processes and the technical processes in which our investigation will be directed and the faces by which our artistic object will pass until transforming itself into a work that can give sustainability to our investigation; next we will speak about the content of each chapter: In the first chapter we deal with the conception of the artistic object, here we look for the niches and micro niches necessary for the investigative resolution; we established that sculpture is the perfect discipline for the realization of this work, therefore we divide this chapter into two subtopics, in the first subtopic we deal with the conceptualization of the artistic object, here we investigate international referents, artist who have worked the sculptural part with some type of metallic material; In the second subtopic we focus on national and local references which will help us to guide us and sustain the fundamental bases of our research. In the second chapter we will talk about the conception of the artistic work, we will define and conceptualize the work, we will determine what materials we will use, the dimensions and the support to be used, we will mention superficial features, some main indicators of the work itself and the technical data sheet will be made. As a second point we will enter into the theoretical foundation of the work, here we will carry out an investigation of the field in which we want to work, in this case we will gather fundamental information about electric arc welding, its basic principles, its purposes and processes to be carried out, the personal safety methods, the machinery used in this process and the various uses in various fields. In the third chapter the construction process of the work will be shown, starting with the pre-production, at this point a series of sketches will be made in which the concept that will be given to the work will be analyzed and the one that meets the specific requirements of the subject to be treated will be chosen, In the artistic production we will follow the whole process of construction of the final work, from the realization of the final sketch to the construction of the sculpture by electric arc welding, as a last point we will present the final edition of the work in which there will be a brief description of the process that took the work to reach that point. In the fourth chapter we will talk about the critical approach to the work, we will analyze the process of construction of the work, on the other hand, the work will be exposed through social networks in order to gather information about the reactions of the spectators and at the end we will conclude with a critical analysis of the work itself. As a second point we will make the necessary conclusions through which we will expose the strengths and weaknesses of the creative process, research and artistic production.
El presente proyecto está encaminado a la realización de una obra con carácter investigativo, con la finalidad de dejar una guía para las personas que se interesen por la escultura de metal con la técnica de la soldadura de arco eléctrico; poniéndonos en marcha con el resumen del escrito se realizó en cuatro capítulos; en cada una detallamos los procesos investigativos y los procesos técnicos en los que se encaminan nuestra investigación y las fases por las que pasarán nuestro objeto artístico hasta transformarse en una obra que pueda dar sostenibilidad a nuestra investigación; a continuación hablaremos del contenido de cada capítulo: En el primer capítulo tratamos sobre la concepción del objeto artístico, aquí buscamos los nichos y los micro nichos necesarios para la resolución investigativa; establecimos que la escultura es la disciplina perfecta para la realización de este obra, por ende dividimos este capítulo en dos subtemas, en el primer subtema tratamos sobre la conceptualización del objeto artístico, aquí investigamos referentes internacionales, artista que hayan trabajado la parte escultórica con algún tipo de material metálico; en el segundo subtema nos enfocamos en referentes nacionales y locales los cuales nos ayudarán a guiarnos y sostener las bases fundamentales de nuestra investigación. En el segundo capítulo hablaremos sobre la concepción de la obra artística, definiremos y conceptualizaremos la obra, determinaremos qué materiales utilizaremos, las dimensiones y el soporte a utilizarse, se mencionan rasgos superficiales, algunos indicadores principales de la obra en sí y se realizará la ficha técnica. Como segundo punto entraremos en la fundamentación teórica de la obra, aquí realizaremos una investigación del campo en el que queremos trabajar, en este caso recopilaremos información fundamental sobre la soldadura por arco eléctrico, sus principios básicos, sus finalidades y procesos a llevar a cabo, los métodos de seguridad personal, la maquinaria que se emplean en este proceso y los diversos usos en varios campos. En el tercer capítulo se mostrará el proceso de construcción de la obra, comenzando por la preproducción, en este punto se realizará una serie de bocetos en el cual analizaron el concepto que se le dará a la obra y se elegirá el que cumpla con los requisitos puntuales del tema a tratar, en la producción artística se realizará un seguimiento del todo el proceso de construcción de la obra final, desde la realización del boceto final hasta la construcción de la escultura por medio de la soldadura por arco eléctrico, como último punto se presentará la edición final de la obra en la cual se realizará una breve descripción del proceso que llevó la obra para llegar a ese punto. En el cuarto capítulo hablaremos sobre el abordaje crítico de la obra, analizaremos el proceso de construcción de la obra, por otra parte, la obra se expondrá por medio de redes sociales para poder recopilar información sobre las reacciones de los espectadores y al final concluimos con un análisis crítico sobre la obra en sí. Como segundo punto realizaremos las conclusiones necesarias mediante las cuales expondremos los puntos fuertes y débiles del proceso creativo, investigativo y la producción artística.
Keywords: ESCULTURA; ARCO ELECTRICO; ARTE; ELECTRODO